FEATURES SENSITIVITY OF MICROORGANISMS TO ANTIBIOTICS, WHICH ARE ISOLATED FROM THE SKIN OF THE PATIENT DOGS ON DEMODECOSIS AND OTODEKTSIS - Гаврик, К. А. (Scientific Progress & Innovations, 2014)
The article highlights the features of the species composition of pathogenic microflora of the affected skin, which complicates the course of demodicosis and otodektosis in dogs and set the sensitivity of selected isolates to antibiotics. Microbiota of the skin characterized by akaroses species diversity of microorganisms and gram-negative bacilli represented (44,4 %), Gram-positive cocci (33,3 %), Gram-positive bacilli and yeast-like fungi (11,1 % respectively). Most isolates were susceptible to amoxicillin , oxacillin , erythromycin, lincomycin, doxycycline and fluoroquinolones but resistant to gentamicin .